Kiprah Haji Sulong dalam Pendidikan Islam di Patani - Adetia Andri; Muhammad Farih Fanani (Medan Resource Center, 2022)
Haji Sulong whose full name is Haji Sulong Al-Fathoni or Muhammad bin Haji Abdul Kadir bin Muhammad bin Tuan Minal is a figure of Islamic reformer in Patani. His struggle for reform is reflected in his efforts to renew Islamic education in Patani. He changed the cottage education system which was considered irrelevant and replaced it with the madrasa education system. In addition, Haji Sulong also struggles to maintain the Malay language which is increasingly being eroded in Thai schools. This is certainly interesting to investigate further, considering that Thailand is a country where the majority of the population is Buddhist. Haji Sulong is a reformer who carries a very strong Islamic spirit. This article uses the historical method in its writing. The historical method includes four steps in historical research, namely heuristics or source collection, criticism or verification, interpretation or interpretation, and historiography or historical writing. fight for Islamic education in Patani.